Perception of employee assistance programme (EAP) practitioners towards the effectiveness of the employee assistance programme training programme : a case study in Syarikat Telekom Malaysia Berhad - Mohan, S/O Khrishnan. (Faculty of Computer Science and Information Technology, 2000)
The main purpose of this study is to identify the perception of EAP practitioners towards the effectiveness of in-house training in Telekom Malaysia Berhad. This study focuses on EAP programmers(Employee Assistance Programme) that have been implemented in the Human Resource Division, EAP subdivision at the Headquarters of Telecom Malaysia Berhad since July 2000. The aim of this study is to determine the demographic characteristics and to identify the perception towards the effectiveness of in-house training programme.